2024
DOI: 10.1126/science.adj1914
|View full text |Cite
|
Sign up to set email alerts
|

Joint environmental and social benefits from diversified agriculture

Laura Vang Rasmussen,
Ingo Grass,
Zia Mehrabi
et al.

Abstract: Agricultural simplification continues to expand at the expense of more diverse forms of agriculture. This simplification, for example, in the form of intensively managed monocultures, poses a risk to keeping the world within safe and just Earth system boundaries. Here, we estimated how agricultural diversification simultaneously affects social and environmental outcomes. Drawing from 24 studies in 11 countries across 2655 farms, we show how five diversification strategies focusing on livestock, crops, soils, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 85 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Here, the development of large-scale trials and continuous monitoring may be crucial to shed light on potential joint environmental and social benefits of sustainable land management. For instance, a recent meta-study across 2,655 farms worldwide showed that applying multiple diversification strategies creates more positive outcomes than individual management strategies alone (Rasmussen et al, 2024). et al, 2016) and volatile (Eisenhauer & Weigelt, 2021;Werner et al, 2021) emissions as well as erosion processes (Tegen & Schepanski, 2009).…”
Section: The Top 10 Research Frontiers Related To the Soil Biodiversi...mentioning
confidence: 99%
“…Here, the development of large-scale trials and continuous monitoring may be crucial to shed light on potential joint environmental and social benefits of sustainable land management. For instance, a recent meta-study across 2,655 farms worldwide showed that applying multiple diversification strategies creates more positive outcomes than individual management strategies alone (Rasmussen et al, 2024). et al, 2016) and volatile (Eisenhauer & Weigelt, 2021;Werner et al, 2021) emissions as well as erosion processes (Tegen & Schepanski, 2009).…”
Section: The Top 10 Research Frontiers Related To the Soil Biodiversi...mentioning
confidence: 99%
“…Given that agroecological practices, such as diversification, are associated more frequently with positive socioeconomics outputs [24][25][26], we also compared the economic performance of diversified crop arrangements compared to pure stand crops. Some studies highlight that applying multiple diversification strategies creates more positive outcomes than individual management strategies [27]. We hypothesised that combining intercropping and flower strips on the edges enhances the efficiency of land use, increasing LER (land equivalent ratio), which in turn enhances the profitability of crops.…”
Section: Introductionmentioning
confidence: 99%